Complete Genome Sequence of a Human Enterovirus C99 Strain Isolated from a Healthy Child in Yunnan, China, in 2013 - Zhang, Jie (Microbiol Resour Announc, 2019)
The complete genome sequence of a human enterovirus C99 strain isolated from a healthy child in Yunnan, China, in 2013 was determined. The isolate belonged to genotype C, according to phylogenetic and homogeneity analyses.